Pengamanan Lembaga Pemasyarakatan Terhadap Kemungkinan Terjadinya Pelarian (Studi Kasus Lapas Kelas II A Pekanbaru): Universitas Islam Riau - Novarizal, Riky; Herman, Herman (Sisi Lain Realita, 2019)
This study aims to explain how the correctional institutions strategies in preventing the flight of the inmates and physical security of Pekanbaru Class IIA Penitentiary. From these physical conditions it has an impact on the implementation of safaguards in preventing various disturbances in order, especially in preventing the escape of prisoners. The method used to conduct this research is a qualitative approach with descriptive design whose data is obtained through the process of interviews and flield observations. Key informant in this study was KPLP (head of security for prison). While the informants in this study were guardians and security sections. This study then concluded that there was still something to be done to improve, both physically and human resources so that the realization of an effective security pattern.